Enhancing the Efficiency of Photovoltaic Systems through the Integration of Multiple MPPT Algorithms (INC, P&O, FLC) - HAMIDATOU Abdelkader; SALHI Rafik; DJAGHAL Mohammed khalifa (University of Shahid Hama Lakhdar - El Oued, 2025)
The aim of improving the efficiency of photovoltaic systems is to maximize energy extraction from solar panels using Maximum Power Point Tracking (MPPT) algorithms. These include Perturb and Observe (P&O), which is simple but suffers from oscillations; Incremental Conductance (INC), which offers greater accuracy under dynamic conditions; and the Fuzzy Logic Controller (FLC), which relies on artificial intelligence and provides faster responses to changing environments. Combining these algorithms enhances overall system performance by integrating the simplicity of P&O, the accuracy of INC, and the speed of FLC, thereby increasing the system’s efficiency under various environmental conditions. يهدف تحسين كفاءة الأنظمة الكهروضوئية إلى تعظيم استخلاص الطاقة من الألواح الشمسية باستخدام خوارزميات تتبع نقطة القدرة القصوى (MPPT). وتشمل هذه الخوارزميات خوارزمية الاضط ا رب والم ا رقبة (P&O) ، وهي خوارزمية بسيطة ولكنها تعاني من التذبذبات، وخوارزمية التوصيل الت ا زيدي (INC) ، التي توفر دقة أكبر في الظروف الديناميكية، وخوارزمية التحكم المنطقي الضبابي (FLC) ، التي تعتمد على الذكاء الاصطناعي وتوفر استجابات أسرع للبيئات المتغيرة. يُحسّن دمج هذه الخوارزميات الأداء العام للنظام من خلال دمج بساطة خوارزمية P&O ، ودقة خوارزمية INC ، وسرعة خ وارزمية FLC ، مما يزيد من كفاءة النظام في ظل ظروف بيئية متنوعة .
Master's thesis in electromechanics.2025
Keywords: Photovoltaic systems; Maximum Power Point Tracking (MPPT); Incremental Conductance (INC); Fuzzy Logic Controller (FLC); Energy extraction; Efficiency improvement; الأنظمة الكهروضوئية، تتبع نقطة القدرة القصوى (MPPT) ، التوصيل الت ا زيدي (INC) ، وحدة التحكم المنطقي الضبابي (FLC) استخلاص الطاقة، تحسين الكفاءة.